Problematika Pengembangan Pariwisata Daerahdi Murung Raya, Kalimantan Tengah - Octora, Merrisa (Journal of Indonesian Tourism and Policy Studies, 2016)
Indonesia is well known for its diversity which scattered from east to west. The diversity itself can be considered as the intangible aspects which relates directly with the aspect of tourism. Tourism provides profitable sectors in many countries because tourism has three major functions. First, to support economic aspect by developed local society. Second, to maintain culture and heritage. Third, to preserve the environment, those three aspects will support the strength of the nation. The purpose of this study is to analyze the reason why the tourism aspect cannot be established by following Indonesian tourism strategic planning. This research is using qualitative method to describe the situation from the problem arise within the society and applying descriptive method in analyzing the data particularly for the tourism development. In my writing, I would like to provide argument why the tourism in several areas cannot be fully developed by following the program of sustainable tourism. There are several major factors which can be described as the findings of this research which takes part in Murung Raya, Central Kalimantan such as lack of local empowerment. This is because the local government do not pay attention to the characteristic of particular culture in nearby area as a great cultural heritage, there is no involvement of local society, the allocation of budgeting do not focus on the tourism development, less priority of cultural and tourism aspects from the program of regional strategic development, the tourism development pay less attention to the social regulations and it creates less awareness of the local community about how important tourism to support livelihood as source of alternative income.